804 A Multidisciplinary Approach to Investigating Sleep Practices and Sleep Disturbances on an Inpatient Neurology Unit. (3rd May 2021) - Kadura, Sullafa; Lin, Jennifer; Poulakis, Alexander; Ibarra, Michael; Cai, Xueya; Roberts, Debra
Abstract: Introduction: Minimizing nightly disruptions in the inpatient setting requires a multidisciplinary, collaborative approach. Our aim was to assess staff perceptions and practices of sleep during hospitalization to help identify and prioritize improvement initiatives. Methods: An online survey was distributed to inpatient staff (nurses, residents, attendings, APPs) on a neurology unit at an academic medical center. The survey assessed sleep disturbances, sleep knowledge and sleep practices. Responses across groups were analyzed using Cochran Armitage tests. Cumulative logit model was also performed. Results: Among the 49 respondents, 75% reported not having the training to diagnose and treat sleep disorders. 51.2% rarely or never asked about sleep quality or duration prior to admission. 29.6% rarely or never tracked the amount and quality of sleep during hospitalization. Reasons for not tracking or considering sleep included "not being a priority", "no place to document" and "not being there at night." Overall, staff ranked noise, testing and vital sign checks as most disruptive to sleep quality and temperature as least disruptive. However, nurses perceived medication administration (p=0.0001) and testing (p=0.0296) more disruptive than the ordering providers. Multivariable analysis showed nurses ranked medication administration higher than providers when shift differences were controlled (p< 0.01). Evening/night shift workers ranked pain (p=0.0324) and anxiety (p=0.0360) higher than day shift workers. Those comfortable with diagnosing and treating sleep disorders were more likely to track sleep during admission (p=0.009), allow patients to sleep during medication administration times (p=0.0189) and allow sleep during scheduled lab draws (p=0.0189). Conclusion: Our findings indicate that differences in sleep knowledge and sleep perspectives exist across the healthcare team. Possible explanations include training differences, ordering providers not knowing what time medications are administered or when tests are done, teams not clarifying whether nighttime orders are critical and nurses lacking empowerment to notify providers that sleep is being disrupted. Hand offs may need optimization with regards to pain and anxiety. A multidisciplinary approach, particularly between providers/nurses and night/day teams is critical to improve sleep on inpatient units. Our next steps include surveying patients, tracking nightly disruptions using EMR and decreasing unnecessary overnight orders using a team based approach. Support (if any):